The Importance of Self-Awareness in Building Personal Branding of Brawijaya University Students through Instagram - Wiryananta, Kresna; Safitri, Reza; Prasetyo, Bambang Dwi (Technium Social Sciences Journal, 2021)
This study aims to analyze the effects of the Self-Awareness Outcomes Questionnaire (SAOQ) in building the personal branding of Brawijaya University students through social media Instagram. The research sample used a random sampling technique consisting of 283 students from various faculties. The method used in this research is descriptive quantitative. The Self-Awareness Outcomes Questionnaire (SAOQ) is divided into sub-variables reflective of self-development, acceptance, proactive at work and emotional cost. The results showed that reflective self-development, acceptance, proactive at work and emotional cost had a significant influence in building the personal branding of Brawijaya University students through social media Instagram. It can be concluded that the interest of Brawijaya University students in building personal branding through Instagram is importance by reflective self-development, acceptance, proactive at work and emotional costs.